Construção e validação de protocolo de prevenção de lesão de pele decorrente do posicionamento cirúrgico - Cauduro, Graziela Maria Rosa (2024)
This research aimed to study the prevention of pressure injuries resulting from surgical positioning. This is a prevalent adverse event among patients during the intraoperative period. Planning and implementing strategies to prevent these injuries are essential for patient safety and the quality of surgical care. Therefore, care protocols are tools that assist in the management of nursing care and standardize the care provided. Objective: To build and validate a CareEducational Technology, in the format of an intraoperative care protocol, for the prevention of pressure injuries resulting from surgical positioning aimed at the multidisciplinary team. Method: Methodological research carried out in the following steps: 1) Integrative review of the literature to survey the strategies used by the nursing team to prevent pressure injuries in surgical patients; 2) Construction of the protocol by the work team; 3) Organization of the first version of the protocol according to recommendations; 4) Submission of the first version to the committee of experts for analysis of the adequacy of the content; 5) Preparation of the second version of the protocol; 6) Pre-test of the instrument in the target population; 7) Construction of the final version of the protocol; and 8) Implementation of the protocol. The protocol was developed in conjunction with the work team and was validated by experts for clarity and relevance, with each item scored from 1 to 4 on a Likert scale. The results were evaluated using the Content Validity Index, with an agreement level equal to or greater than 0.80 to ensure validation of the material. Results: The Care-Educational Technology was developed in the format of a care protocol, analyzed by six nurses specialized in the area of pressure injuries and Surgical Block. The content validity index obtained for the different proposed items ranged from 80 to 100%. The protocol consisted of information on concepts, objectives, justification, attributions, team competencies, inclusion criteria, flowchart and indicator. It also included the application of the Risk Assessment Scale for the Development of Surgical Positioning Injuries (ELPO). The experts' suggestions considered pertinent were accepted, which resulted in the Technical and Technological Product: Protocol for the prevention of pressure injuries resulting from surgical positioning. Conclusion: In the evaluation, the protocol proved to be valid for preventing the risks of complications resulting from surgical positioning, enabling its use as an important strategy for standardizing care and procedure safety, contributing to clinical and scientific practice. In addition, it constitutes a tool to be used to qualify intraoperative care and improve the safety of surgical patients.